2005
DOI: 10.1590/s0102-37722005000300004
|View full text |Cite
|
Sign up to set email alerts
|

Crianças e adolescentes vivendo com HIV/Aids e suas famílias: aspectos psicossociais e enfrentamento

Abstract: de crianças e adolescentes soropositivos infectados pela transmissão vertical; descrever dificuldades e estressores percebidos pelos cuidadores sobre aspectos psicossociais e do tratamento para o HIV e analisar estratégias de enfrentamento utilizadas. Participaram 43 cuidadores primários, a maioria (N = 24) mães soropositivas; a idade variou de 18 a 68 anos. Os instrumentos incluíram entrevista semi-estruturada e a Escala Modos de Enfrentamento de Problemas (EMEP). Os resultados revelaram a presença de dificul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
34

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 20 publications
0
4
0
34
Order By: Relevance
“…A similar fact was observed in a research with caregivers of children and adolescents living with HIV/AIDS, which indicated satisfaction with the social support received, especially emotional, as opposed to the instrumental support, which covered financial aid and help in practical and operational aspects of everyday life. 19 The main sources of social support were friends and family not living in the same household. Spouses/partners were not the most mentioned people, probably as a result of AIDS, often occurring amongst couples with different HIV status, where there is a tendency of the not revealing the diagnosis to the spouse, due to stigma and fear of abandonment.…”
Section: 14mentioning
confidence: 99%
“…A similar fact was observed in a research with caregivers of children and adolescents living with HIV/AIDS, which indicated satisfaction with the social support received, especially emotional, as opposed to the instrumental support, which covered financial aid and help in practical and operational aspects of everyday life. 19 The main sources of social support were friends and family not living in the same household. Spouses/partners were not the most mentioned people, probably as a result of AIDS, often occurring amongst couples with different HIV status, where there is a tendency of the not revealing the diagnosis to the spouse, due to stigma and fear of abandonment.…”
Section: 14mentioning
confidence: 99%
“…Entretanto, poucas são as pesquisas que enfocam os adolescentes contaminados, em especial os seus aspectos psicológicos [8][9][10] . Estudos realizados no Brasil são ainda mais raros [11][12][13] . A presente pesquisa busca avaliar esses aspectos psicológicos, focando-se na avaliação da satisfação de vida de jovens portadores do vírus HIV.…”
Section: Introductionunclassified
“…Verifica-se na literatura que muitas famílias podem passar por processos de reorganização do núcleo familiar, quando um dos pais biológicos, ou ambos, vem a falecer em decorrên-cia das complicações advindas da Aids (43,44). É possível que o impacto trazido por esse tipo de reorganização familiar gere situações concorrentes à adesão e contextos adversos ao uso dos medicamentos.…”
Section: Antecedentes Do Conceito Adesão Ao Tratamento De Crianças Sounclassified